2021
DOI: 10.1111/jopr.13363
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Students’ Performance in Preclinical Fixed Prosthodontics Course in Predicting Subsequent Clinical Performance

Abstract: Purpose To evaluate the correlation between students’ achieved grades in a preclinical fixed prosthodontics course and their performance in the same discipline's clinical courses. Materials and methods This study was conducted in 2019 on 76 students who passed all preclinical and clinical fixed prosthodontics courses. Their final examination grades in preclinical and clinical prosthodontics courses were compiled and made anonymous. The Statistical Package for the Social Sciences (SPSS Version 23) was used to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The lack of relationship between first‐year preclinical science GPA as well as first‐year preclinical laboratory GPA and overall clinical science GPA supports previous research indicating a lack of relationship between preclinical and clinical performance 3,11 . However, it is in contrast to previous research that suggests that clinical performance may be predicted by preclinical performance, 10 particularly in operative dentistry 7,9 and fixed prosthodontics 7,8 . Further investigations on the genesis of student success in the latter years of the predoctoral dental program are warranted.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…The lack of relationship between first‐year preclinical science GPA as well as first‐year preclinical laboratory GPA and overall clinical science GPA supports previous research indicating a lack of relationship between preclinical and clinical performance 3,11 . However, it is in contrast to previous research that suggests that clinical performance may be predicted by preclinical performance, 10 particularly in operative dentistry 7,9 and fixed prosthodontics 7,8 . Further investigations on the genesis of student success in the latter years of the predoctoral dental program are warranted.…”
Section: Discussionsupporting
confidence: 62%
“…3,11 However, it is in contrast to previous research that suggests that clinical performance may be predicted by preclinical performance, 10 particularly in operative dentistry 7,9 and fixed prosthodontics. 7,8 Further investigations on the genesis of student success in the latter years of the predoctoral dental program are warranted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enter the dilemma if competency for clinical procedures can be simulated and demonstrated on typodonts. In the context of prosthetic dentistry, it was shown that work done of manikins in an educational program is a statistically significant clinical predictor for clinical performance in FPD 17 . Other discussions regarding the use of live patients to determine competency during licensing exams led in year 2000 to the passage of a resolution in the American Dental Association's House of Delegates calling for an end to this practice by the year 2005 18 .…”
mentioning
confidence: 99%